2004
DOI: 10.1007/s00421-004-1054-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent hypoxia on oxygen uptake during submaximal exercise in endurance athletes

Abstract: The purpose of the present study was to clarify the following: (1) whether steady state oxygen uptake (VO(2)) during exercise decreases after short-term intermittent hypoxia during a resting state in trained athletes and (2) whether the change in VO(2) during submaximal exercise is correlated to the change in endurance performance after intermittent hypoxia. Fifteen trained male endurance runners volunteered to participate in this study. Each subject was assigned to either a hypoxic group (n=8) or a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
78
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 31 publications
14
78
2
3
Order By: Relevance
“…Although an unchanged economy following LHTL has been reported previously (39), it is difficult to explain the difference with the studies in which a reduced submaximal exercise VO 2 has been observed (19,28,29,52,53). Nevertheless, none of these studies provides an objective description of training intensity, which was either controlled by subjective feedback from the athletes (19,52) or not at all (28,29,53). It is therefore appealing to speculate that the open-label treatment and a concomitant placebo effect motivated LHTL subjects to train harder than their control counterparts, which in turn, may have improved running economy (15).…”
Section: Potential Mechanisms Underlying Lhtlcontrasting
confidence: 45%
See 1 more Smart Citation
“…Although an unchanged economy following LHTL has been reported previously (39), it is difficult to explain the difference with the studies in which a reduced submaximal exercise VO 2 has been observed (19,28,29,52,53). Nevertheless, none of these studies provides an objective description of training intensity, which was either controlled by subjective feedback from the athletes (19,52) or not at all (28,29,53). It is therefore appealing to speculate that the open-label treatment and a concomitant placebo effect motivated LHTL subjects to train harder than their control counterparts, which in turn, may have improved running economy (15).…”
Section: Potential Mechanisms Underlying Lhtlcontrasting
confidence: 45%
“…However, we found no indications for LHTL to affect whole-body VO 2 during submaximal cycling performed on numerous occasions. Although an unchanged economy following LHTL has been reported previously (39), it is difficult to explain the difference with the studies in which a reduced submaximal exercise VO 2 has been observed (19,28,29,52,53). Nevertheless, none of these studies provides an objective description of training intensity, which was either controlled by subjective feedback from the athletes (19,52) or not at all (28,29,53).…”
Section: Potential Mechanisms Underlying Lhtlmentioning
confidence: 48%
“…In addition, not only HVR but also cardiovascular responses to hypoxia might be an underlying mechanism. HVR and systolic blood pressure responses were significantly increased after a 2-week intermittent hypoxic training program (5 sessions per week; 30 min per day; 70% _ VO 2 max ; 4,500 m), but decreased significantly in a normoxic control group (Katayama et al 2004). However, it could be that other peripheral muscle factors are associated with the changes observed following the training in hypoxia.…”
Section: Effects Of Training In Hypoxia or Normoxia On Endurance Perfmentioning
confidence: 95%
“…Previous studies have used fixed F I O 2 values (Katayama et al 2001(Katayama et al , 2004, or a graded decline in F I O 2 Hinckson et al 2007;Julian et al 2004) as the hypoxic stimulus during IHE. Under poikilocapnic conditions i.e.…”
Section: Effects Of Ihe On Gas Exchangementioning
confidence: 99%